2023
DOI: 10.3390/ma16072935
|View full text |Cite
|
Sign up to set email alerts
|

IBIL Measurement and Optical Simulation of the DI Center in 4H-SiC

Abstract: In this paper, DI defects are studied via experiments and calculations. The 2 MeV H+ is used to carry on an ion-beam-induced luminescence (IBIL) experiment to measure the in-situ luminescence of untreated and annealed 4H-SiC at 100 K. The results show that the luminescence intensity decreases rapidly with increasing H+ fluence, which means the losses of optical defect centers. In addition, the evident peak at 597 nm (2.07 eV) is the characteristic peak of 4H-SiC, and the weak peak between 400 nm and 450 nm is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In prior research at Beijing Normal University, various experiments have been successfully implemented in the IBIL measurement system to investigate the effects of flux and temperature on the luminescence of low-concentration rare earth elements and defects. [21][22][23][24][25] Branson et al conducted a study on the luminescence of In-GaN/GaN using IBIL, PL and cathodeluminescence measurement methods, and found that luminescence intensity depends on the specific excitation method employed in each measure-ment technique. [18] In this study, IBIL spectra of GaN/Al 2 O 3 at various depths were acquired by adjusting the incident ion energy to adapt to different film thicknesses.…”
Section: Introductionmentioning
confidence: 99%
“…In prior research at Beijing Normal University, various experiments have been successfully implemented in the IBIL measurement system to investigate the effects of flux and temperature on the luminescence of low-concentration rare earth elements and defects. [21][22][23][24][25] Branson et al conducted a study on the luminescence of In-GaN/GaN using IBIL, PL and cathodeluminescence measurement methods, and found that luminescence intensity depends on the specific excitation method employed in each measure-ment technique. [18] In this study, IBIL spectra of GaN/Al 2 O 3 at various depths were acquired by adjusting the incident ion energy to adapt to different film thicknesses.…”
Section: Introductionmentioning
confidence: 99%